2021
DOI: 10.1177/15248380211013135
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious Trauma Experienced by Health Care Providers Involved in Traumatic Childbirths: A Meta-Synthesis

Abstract: Health care providers are often “second victims” of traumatic childbirth events and should be adequately supported by their organizations to alleviate occupational stress and burnout. Therefore, this review aimed to explore and understand the vicarious traumatic childbirth experiences of health care providers, including obstetricians, midwives, nurses, and students. A systematic review of qualitative studies was conducted. Seven electronic databases, namely, PubMed, CINAHL, Embase, PsycINFO, Cochrane, Scopus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 83 publications
0
9
0
1
Order By: Relevance
“…33 Where ni = required number of study participants from a given hospital, Ni = required sample size for the study, Nt = total number of deliveries from all the selected hospitals, and n = number of deliveries as per hospital. The total number of deliveries in the selected health facilities (n = 3506) the sample size of 307 was proportionately allocated to the eight health facilities selected and therefore, 201, 40,20,15,11,8,6, and 5 study participants were selected from each of the selected hospitals. Study participants from the selected hospitals were selected using convenience sampling method.…”
Section: Sample Size Determination and Sampling Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Where ni = required number of study participants from a given hospital, Ni = required sample size for the study, Nt = total number of deliveries from all the selected hospitals, and n = number of deliveries as per hospital. The total number of deliveries in the selected health facilities (n = 3506) the sample size of 307 was proportionately allocated to the eight health facilities selected and therefore, 201, 40,20,15,11,8,6, and 5 study participants were selected from each of the selected hospitals. Study participants from the selected hospitals were selected using convenience sampling method.…”
Section: Sample Size Determination and Sampling Methodsmentioning
confidence: 99%
“…Such conditions include high ratio between patients and providers (too few providers, too many patients), lack of access to life saving medications and supplies, 14,15 lack of involvement of birth partners (companionship) due to adapted colonial policy, [16][17][18] limited preparation or knowledge at the community level about pregnancy/labor/birth, 19 these conditions leads to stressful and often traumatic to healthcare provider, which sometimes might be associated with childbirth violence. 20,21 The observed poor behaviors from some providers may be learned behaviors from other health workers and also likely a result of chronic stress and trauma from hard-working environmental and other factors. 20 Respectful maternity care (RMC) is a universal right of childbearing women as every woman should be treated with dignity and respect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gladden Model of Teaching Trauma Content, presented in Supplemental Appendix A, includes responsibilities to be completed across three levels of influence: university or department level, teacher level, and student level. Although none of the reviewed articles discussed university-and department-level responsibilities, the importance of organizational structure and support in mitigating the risk for adverse consequences from exposure to trauma content across providers has been documented in multiple systematic reviews (Molnar et al, 2020;Shorey & Wong, 2021. For example, research has documented the role of the organizational resources and support in assisting mental health professionals and reducing compassion fatigue (Singh et al, 2020). Subsequently, the model includes general recommendations for universities and departments to help minimize the potential for adverse consequences and support instructors and students, such as considering the times of courses and class size.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Nonetheless, no systematic review has documented how well-prepared students are to deal with trauma exposure in the field. However, systematic reviews have shown a range of adverse consequences after exposure to trauma in the workplace across providers, including mental health workers (Singh et al, 2020), professionals serving trauma survivors (Cieslak et al, 2014), child welfare workers (Molnar et al, 2020), health care workers (Shorey & Wong, 2021), and physicians (van Mol et al, 2015). These studies suggest the need to prevent providers from experiencing vicarious trauma, compassion fatigue, burnout, and secondary traumatic stress.…”
mentioning
confidence: 99%